Prevalence of carriage of community-acquired Methicillin-resistant Staphylococcus aureus among children attending the pediatric OPD at a tertiary care hospital - Radhakrishnan, Vishnurajan; Ravichandran, Saranya; Vadivelu, Senthamarai Murugaiyan; Radhakrishnan, Shankar (International Journal of Contemporary Pediatrics, 2018)
Background: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections are commonly recognized in persons without traditional risk factors. Nasal carriage of MRSA is an important risk factor for subsequent MRSA infection and transmission of this pathogen. The aim of this study was to estimate the prevalence of carriage of community acquired MRSA and to describe its antibiotic susceptibility pattern among the pediatric population. Methods: A prospective longitudinal study was conducted in our hospital for a period of 6 months. All pediatric patients age less than 15 years attending the pediatric OPD were included in the study. A total of 325 children were included in the study based on our inclusion and exclusion criteria. Nasal smear was collected by tilting back the child’s head and gently inserting a sterile cotton swabs pre-wetted with sterile saline and slowly rotating against the turbinate of both anterior nares. The following antibiotics were tested for sensitivity pattern: penicillin, pipercillin, erythromycin, clindamycin, cotrimoxazole, vancomycin, linezolid, rifampin, ciprofloxacin and daptomycin. Any S. aureus that is resistant to Cefoxitin was defined as MRSA. Results: The prevalence of Staphylococcus aureus was found to be 26.7% of the entire microorganism detected and 6.4% (n = 21) of the entire study subjects had methicillin resisitant Staphylococcus aureus. Of testing the susceptibility of the various antibiotics vancomycin was the only drug found to be 100% sensitive followed by linezolid and pipericillin (90%). 50% sensitivity was seen with erythromycin and very poor sensitivity was seen in cefuroxime and ciprofloxacin (<50%). Conclusions: CA-MRSA strains tend to replace HA-MRSA in health-care settings, making infection control measures less effective. Hospital based antibiotic policy has to be created and strictly followed to minimize the burden of antibiotic resistance.